A CORRELATION BETWEEN VOCABULARY MASTERY AND EMOTIONAL INTELLIGENCE TOWARDS READING COMPREHENSION - Diah Resmisari; Julyanta Br Sitepu (STIBA IEC JAKARTA, 2022)
This research aims to prove a correlation between Vocabulary Mastery and Emotional Intelligence towards Reading Comprehension (Survey of State Junior High School Students in Bekasi Regency). This research employs a survey of regression and correlation analysis using the SPSS program. There are three variables in this research: two independent variables (vocabulary mastery and emotional intelligence), and one dependent variable (reading comprehension). The data is gathered through vocabulary and reading comprehension tests, as well as a questionnaire on emotional intelligence. Following an analysis of the research variables, the following conclusion can be drawn: (1) There is a significant correlation of vocabulary mastery and emotional intelligence together on students' ability to understand English reading as evidenced by the acquisition of Sig scores. 0.000 < 0.05 and Fh= 20.095 or 29.3%, (2) there is a significant correlation of vocabulary mastery on students' ability to understand English reading as evidenced by the acquisition of Sig scores. 0.002 < 0.05 and t-test= 3.164 or 14.45%, (3) there is a significant correlation of emotional intelligence on the ability to understand students' English reading as evidenced by the acquisition of Sig scores. 0.002 < 0.05 and t-test= 3.233 or 14.87%.